Midwifery Qualification in Selected Countries: A Rapid Review - Shakirah Md. Sharif; Wuan Shuen Yap; Weng Hong Fun; Ee Ling Yoon; Nur Fadzilah Abd Razak; Sondi Sararaks; Shaun Wen Huey Lee (MDPI AG, 2021)
Background: While the global maternal mortality ratio (MMR) shows a decreasing trend, there is room for improvement. Midwifery education has been under scrutiny to ensure that graduates acquire knowledge and skills relevant to the local context. Objective: To review the basic professional midwifery qualification and pre-practice requirements in countries with lower MMR compared with Malaysia. Methods: A rapid review of country-specific Ministry of Health and Midwifery Association websites and Advanced Google using standardised key words. English-language documents reporting the qualifications of midwives or other requirements to practise midwifery from countries with a lower MMR than Malaysia were included. Results: Sixty-three documents from 35 countries were included. The minimum qualification required to become a midwife was a bachelor's degree. Most countries require registration or licensing to practise, and 35.5% have implemented preregistration national midwifery examinations. In addition, 13 countries require midwives to have nursing backgrounds. Conclusion: In countries achieving better maternal outcomes than Malaysia, midwifes often have a degree or higher qualification. As such, there is a need to reinvestigate and revise the midwifery qualification requirements in Malaysia.